2015
DOI: 10.4187/respcare.03367
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Impairment in Neuromuscular Disease Using an Expiratory/Inspiratory Pressure Ratio

Abstract: BACKGROUND: Neuromuscular diseases (NMDs) lead to different weakness patterns, and most patients with NMDs develop respiratory failure. Inspiratory and expiratory muscle strength can be measured by maximum static inspiratory pressure (P Imax ) and maximum static expiratory pressure (P Emax ), and the relationship between them has not been well described in healthy subjects and subjects with NMDs. Our aim was to assess expiratory/inspiratory muscle strength in NMDs and healthy subjects and calculate P Emax /P I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 13 publications
3
13
0
2
Order By: Relevance
“…In contrast, in the control group, MEP decreased to a greater extent than MIP did, after 8 weeks. This result coincides with findings obtained by a previous study, which reported that expiratory muscle strength decreases to a greater extent than inspiratory muscle strength in patients with NMD4, 13 ) .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, in the control group, MEP decreased to a greater extent than MIP did, after 8 weeks. This result coincides with findings obtained by a previous study, which reported that expiratory muscle strength decreases to a greater extent than inspiratory muscle strength in patients with NMD4, 13 ) .…”
Section: Discussionsupporting
confidence: 93%
“…MEP in MEP/MIP was reported to be greater than MIP in both the healthy control group and patients with NMD13 ) . In this study, MEP in MEP/MIP was also greater than MIP in both the experimental and control groups.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The measurement of MIP and MEP is quick, non-invasive, and normal values have been established 5 . A recent study showed higher MEP values in comparison to MIP in patients with neuromuscular diseases; in this work, the MEP/MIP ratio was 1.33 ± 0.62 in patients with ALS and differed from those observed in other neuromuscular conditions 4 .…”
mentioning
confidence: 42%
“…furthermore, some ALS patients have significant upper motor neuron dysfunction, while others have little 4 . Severe weakness leads to breathlessness and ventilatory failure.…”
mentioning
confidence: 99%